Electronic Tuning and Catalytic Activity of a Novel Pd(II) Complex Supported by a Tetracoordinate Ligand. Issue 46 (11th December 2018) - Maity, Lakshmikanta; Parua, Sankar Prasad; Rana, Bidyut Kumar; Isab, Anvarhusein A.; Bielawski, Christopher W.; Dinda, Joydev
Abstract: The synthesis and study of a novel Pd(II) complex (2 ) supported by a new tetracoordinate ligand that is based on a bis(N‐heterocyclic carbene) with two pendant pyrimidinyl donors is described. The complex was characterized using a series of spectroscopic, analytical, and computational techniques. A preliminary assessment showed that2 displayed good performance in Suzuki‐Miyaura coupling reactions between phenyl boronic acid and an assortment of substituted bromobenzenes. Finally, the intrinsic electronic characteristics of the complex were elucidated through DFT‐based molecular orbital calculations which revealed that the coordinated metal center was relatively electron deficient and stabilized by a series of ligand dominated interactions. Abstract : A novel Pd(II) complex supported by tetracoordinate ligand that is based on a bis(N‐heterocyclic carbene) outfitted with pyrimidinyl groups is described. The complex was characterized by spectroscopic, analytical, and computational techniques and its catalytic activity was assessed in a range of contemporary coupling reactions.